2015
DOI: 10.1017/jfm.2015.584
|View full text |Cite
|
Sign up to set email alerts
|

Lift and drag in two-dimensional steady viscous and compressible flow

Abstract: This paper studies the lift and drag experienced by a body in a two-dimensional, viscous, compressible and steady flow. By a rigorous linear far-field theory and the Helmholtz decomposition of the velocity field, we prove that the classic lift formula L = −ρ 0 UΓ φ , originally derived by Joukowski in 1906 for inviscid potential flow, and the drag formula D = ρ 0 UQ ψ , derived for incompressible viscous flow by Filon in 1926, are universally true for the whole field of viscous compressible flow in a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…That γ v depends on q 1 /q 2 and q v on γ 1 /γ 2 is expected from the coupled sheet strength evolution equations in (24). In particular, we expect that θ 1 ≤ θ v ≤ θ 2 and since q ≥ 0, then entrainment of irrotational fluid acts to decrease the vortex sheet strength of the shed sheet by 'diffusing' the previously existing vorticity in the sheet.…”
Section: Separation At the Sharp Edgementioning
confidence: 83%
See 1 more Smart Citation
“…That γ v depends on q 1 /q 2 and q v on γ 1 /γ 2 is expected from the coupled sheet strength evolution equations in (24). In particular, we expect that θ 1 ≤ θ v ≤ θ 2 and since q ≥ 0, then entrainment of irrotational fluid acts to decrease the vortex sheet strength of the shed sheet by 'diffusing' the previously existing vorticity in the sheet.…”
Section: Separation At the Sharp Edgementioning
confidence: 83%
“…Evidently the evolution of the sheets are coupled to each other through the quantity µ, which partly represents the jump in dynamic pressure. For the vortex sheet (24) represents the familiar result that tangential pressure gradients generate vorticity components bi-normal to the gradient direction [23]. For the entrainment sheet the pressure jump acts to 'push' or entrain fluid into the sheet.…”
Section: Evolution Equations For the Sheet Strengthsmentioning
confidence: 99%
“…They found that the lift calculated by K-J formula (1.2), with ∇φ replaced by the measured total disturbance velocity u ′ , is a good approximation to that of the real viscous flow for typical aerodynamic applications: (1.5) in which V is the volume enclosed by S. Moreover, the experiment confirmed that Γ may still be independent on S. In his theoretical explanation, Taylor (1926) points out that these positive answers require two conditions: (a) the intersect of S and the wake has to be a vertical plane ("wake plane", denoted by W ) with normal n = e x ; and (b) the net vorticity flux through W must vanish, which can be proven for steady viscous flow at large Reynolds number (for an improved proof of this issue see Wu, Ma & Zhou 2015). We call these conditions the first and second Taylor criteria (Liu, Zhu & Wu 2015), and (1.4) the approximate Taylor lift formula. Independent of the work of Taylor (1926), Filon (1926) makes a thorough analysis of the lift and drag problem for two-dimensional, viscous, incompressible and steady flow.…”
Section: Far-field Force Theory In Two Dimensionsmentioning
confidence: 99%
“…where φ f is the dominant term in the far-field, which may be multi-valued or singular, and φ r is the single-valued regular term, which decays faster than φ f at the far-field but may play a crucial role in the near-field. In particular, for two-dimensional incompressible flow, there is (Liu, Zhu & Wu 2015)…”
Section: Three-dimensional Vorticity Far Field and Singularitymentioning
confidence: 99%
“…It has now become a challenge to investigate the effects of compressibility on the lift and lift-induced drag. For instance, with a linear far-field analysis, Liu et al [12,13] recently showed that the Kutta-Joukowski theorem still holds in compressible steady viscous flows. More recently, Schmitz proposed an extension of the Kutta-Joukowski theorem in viscous incompressible flows [14].…”
mentioning
confidence: 99%